Badiou(S): Views on a Kaleidoscopic Life; [Badiou(S): Miradas Sobre Una Vida Caleidoscópica] - Letelier-Soto, A (Universidad Compultense Madrid, 2023)
Referring to multiplicity is a commonplace when it comes to Alain Badiou’s work, since it is a production of a notorious complexity and the exploration of its various facets is to enter a universe of multiple dimensions. In this sense, it is proposed to compare his production with a kaleidoscope, an artifact that reveals multiplicity as the essence of unity and, at the same time, confers meaning to that diversity. This kaleidoscopic multiplicity is not limited only to the figure of the intellectual and his writings, but expands into other spheres. Indeed, when analyzing his early works and the beginnings of his intellectual trajectory, the influence of Sartre becomes evident, as well as his later connections with French structuralism and, in particular, with the figure of Louis Althusser. On the other hand, it is interesting to note here that Badiou’s productions, far from being enclosed in academic debates, are intertwined with topics such as the question of love, which is directly connected with the rest of his theoretical and political reflections. Thus, it is of interest here to appreciate this particular intersection that allows a deeper understanding of his thought and his radical concern for the social. © 2023, Universidad Compultense Madrid. All rights reserved.